2013
DOI: 10.1111/dme.12129
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Behaviour subscale of the Hypoglycaemia Fear Survey: an international study

Abstract: The HFS Worry subscale measures one construct of anxiety about various aspects of hypoglycaemia. In contrast, the HFS Behaviour subscale appears to measure two distinct aspects of behavioural avoidance to prevent hypoglycaemia, actions which maintain high blood glucose and other behaviours to avoid hypoglycaemic risk. These results demonstrate the clinical importance of the HFS Behaviour subscales and their differential relationships with measures of diabetes outcome such as HbA1c .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 24 publications
4
60
0
2
Order By: Relevance
“…More recently, there has been a focus on disease-specific psychosocial issues. In particular, diabetes distress (11,12), reluctance to start insulin (13,14), and fear of hypoglycemia (15,16) have been addressed. This research has been advanced significantly by a multinational survey called Diabetes Attitudes, Wishes and Needs (DAWN).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, there has been a focus on disease-specific psychosocial issues. In particular, diabetes distress (11,12), reluctance to start insulin (13,14), and fear of hypoglycemia (15,16) have been addressed. This research has been advanced significantly by a multinational survey called Diabetes Attitudes, Wishes and Needs (DAWN).…”
Section: Introductionmentioning
confidence: 99%
“…Fear of hypoglycemia has also been shown to influence self-care behavior as patients attempt to avoid hypoglycemia by running high blood glucose values, increasing carbohydrate intake, omitting or reducing the dosage of insulin or avoiding physical activity [2,[6][7][8]. Ultimately, such changes in self-care behavior may also result in deteriorating glycemic control [9], although this has not been consistently demonstrated in adults [10].…”
Section: Introductionmentioning
confidence: 99%
“…16 The multidimensionality of the HFS-B subscale has been further proven in an international study. 14 This study also showed that the reliability (internal consistency and test-retest reliability) for HFS-B was lower than for HFS-W. It suggests that HFS-B is less coherent and stable than HFS-W.…”
Section: Discussionmentioning
confidence: 57%
“…Previously, the HFS-II instrument has been developed and validated mainly among patients with type 1 diabetes. [13][14][15][16] It is based on concerns that patients with type 1 diabetes receiving intensive insulin therapy may have different experiences with hypoglycemia and insulin dose adjustments compared with patients with type 2 diabetes receiving less intensive insulin regimens, such as basal insulin in combination with oral glucose-lowering medications. In our sample, only 10.5% of patients with type 2 diabetes were on basal insulin only, with the majority on more intensive insulin regimens.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation